Pemberdayaan Pemuda Berbasis Karang Taruna Sebagai Upaya Mewujudkan Sustainable Development Goals Desa (Studi di Desa Karet Jaya Kecamatan Buay Pemaca Kabupaten OKU Selatan) - Anggun Rizky Yani; Yahnu Wiguno Sanyoto; Eva Susanti (Jurnal Ilmu Pemerintahan, 2026)
Youth have an important role as agents of change in village development, therefore the existence of Karang Taruna as a youth empowerment institution becomes very strategic in supporting the achievement of Village Sustainable Development Goals (SDGs), especially Goal 17, namely partnerships for village development. However, in Karet Jaya Village, Buay Pemaca District, Ogan Komering Ulu Selatan Regency, the role of Karang Taruna has not functioned optimally, resulting in low youth participation in village development. This study aims to analyze the implementation of Village SDGs Goal 17 through strengthening Karang Taruna institutions in youth empowerment and to identify the factors influencing it. This research was conducted in 2026 using a descriptive qualitative method. Data were collected through observation, interviews, and documentation involving village government officials, Karang Taruna administrators, religious leaders, community leaders, academics, and the general public. The findings show that the strengthening of individual youth capacity has not been supported by sustainable guidance, youth solidarity and cooperation are still situational, and access to facilities, information, and village funding remains limited. These conditions indicate that the partnership between the village government and youth has not been established optimally. Strengthening Karang Taruna institutions, improving village policy transparency, and expanding youth participation are important steps to achieve sustainable village development. Keywords: Youth Empowerment, Karang Taruna, Village SDGs, Village Partnership